Unleashing potential: evaluating the effectiveness of the BOPPPS teaching strategy in Chinese urology education - Zhang, Rong-ling; Gan, Kai; Zuo, Hong; Han, Donghui; Shi, Kang; Wang, Jing; Zhang, Keying; Jiang, Wenkai; Wang, Diya; Li, Yu (Frontiers in Medicine, 2025)
IntroductionThe BOPPPS teaching strategy has gained popularity in medical education in China as a more effective and practical pedagogy. However, its impact on knowledge acquisition and clinical skills in urology education has not been comprehensively evaluated. This study seeks to assess the effectiveness of the BOPPPS strategy in comparison to traditional lecture-based learning (LBL) during clinical internships in Chinese urology education, utilizing meta-analysis for verification.MethodsA cohort of 96 clinical medicine students from Xijing Hospital, engaged in clinical practice at the Department of Urology from September 2022 to June 2023, were stratified into two groups and exposed to identical teaching materials. The experimental group (n=48) was instructed using the BOPPPS model, while the control group (n=48) adhered to traditional instructional methods. Data on student satisfaction and self-assessment of the course were collected through a questionnaire, and end-of-course performance was evaluated through a post-study examination. We used meta-analysis aimed to evaluate the overall effectiveness of the BOPPPS teaching strategy compared to LBL teaching in surgery-related medical education.ResultsThe experimental group, which received instruction using the BOPPPS teaching model, achieved significantly higher scores in theoretical knowledge assessments and clinical practical skills compared to the control group. Additionally, the experimental group demonstrated greater levels of interaction with both teachers and students, with instructors displaying a higher ability to foster independent thinking among students. Furthermore, the teaching process in the experimental group was found to utilize classroom time more efficiently in comparison to the control group. And we confirmed that the BOPPPS model demonstrated a greater capacity to stimulate student interest in urology and improve their overall proficiency by meta-analysis.DiscussionThe BOPPPS model exhibits superior efficacy in clinical teaching of urology, thus warranting consideration for wider adoption and dissemination.